Malassezia species infection of the synovium after total knee arthroplasty surgery - Leylabadlo, Hamed Ebrahimzadeh; Zeinalzadeh, Elham; Akbari, Najibeh Asl Rahnemaii; Kafil, Hossein Samadi (German Medical Science GMS Publishing House, 2016)
Infection is a serious complication after implantation of total knee-prostheses. However, fungal infection is rarely found in periprosthetic joints, and in most reports, the infecting organism is a species. This is a case report of infection after left knee total arthroplasty caused by species. The patient is still undergoing antifungal therapy with voriconazole and is still being followed-up. To the authors' knowledge, the present case is the first report of species in a patient after total knee arthroplasty.